From the margins to the mainstream: imagining socioecological futures in Wales - Anna Pigott (2018)
In light of widespread claims about a lack of imagination in response to socioecological crises, this study explores various projects in Wales in order to critically examine the kinds of imaginaries of socioecological transformation that these projects are generating. The Welsh Government’s pioneering Well-being of Future Generations Act (2015) provides the context for the research, and this study presents the ﬁrst critical analysis of this new legislation, and the imaginaries associated with it. Alongside this analysis, however, the study also takes more marginal projects and practices seriously as forms of “minor theory” that might present alternative ways of doing things. To this end, the study has engaged with a range of projects that are envisioning socioecological transformation, including projects in the arts, alternative agriculture, and renewable energy.The study thus engages with imaginaries of socioecological transformation “from the margins to the mainstream”, not by positing these imaginaries as “unimportant” as opposed to “important” (respectively), but by seeking to give equal attention to the political potential of the kinds of ideas that are in play, and what kinds of socioecological futures these ideas make possible. Collective imaginaries of socioecological crises, and the ideas that sustain them, are an important ﬁeld of struggle with regard to how particular forms of transformation are, or are not, set in motion. The thesis explores three main themes: time and futurity, human–environment relations, and the role of art in socioecological transformation, and shows how notions of complexity, non-linearity, and more-than-human agency emerge as important ideas, and often in unexpected or overlooked places. The research is based on combinations of participant observation, interview, and document analysis, and adopts a standpoint that research does not simply represent how worlds are made, but also participates in their making.